MOTIF DAN KEPUASAN MEMBACA NOVEL PADA APLIKASI WATTPAD DI KALANGAN PEMUDA KOTA DENPASAR - Wahyuni, Prima Sriparta; Alit Suryawati, I Gusti Agung; Pradipta, Ade Devia (E-Jurnal Medium, 2019)
ABSTRACT Wattpad is an online platform that provides varieties of prose essays, such as novels. The presence of Wattpad makes it easy for novel connoisseurs to be able to read novels in digital form. This research aims to find out the motives and the satisfaction of youth in Denpasar City in reading novels on Wattpad. In this study combining motives put forward by Dennis McQuail and Zizi Papacharissi and Alan M. Rubin. The theory used is The Theory Uses and Gratifications. This research is descriptive quantitative method with purposive sampling as the technique. Data obtained by using Likert scale in questionnaire. The result shows five of the seven motives that could be satisfied are entertainment motive, convenience motive, pass time motive, information motive and utility motive. Motives that have not been able to be satisfied are personal identity motive and integration and social interaction motive. Keywords: Denpasar, Motives, Satisfaction, Wattpad, Youth